A grain detection system for grain-oriented electrical steels - Mohd Ali, Borhanuddin; Moses, Anthony John (Institute of Electrical and Electronics Engineers, 1989)
A microcomputer-based apparatus for the detection of grain structures in grain-oriented electrical steels has been developed. The apparatus enables observation of grain structures to be made through the stress coatings. The localized magnetic field distribution on the surface of the electrical steel is mapped using a pair of monolithic thin-film magnetoresistive heads (MRHs) made from Permalloy (82%-18% Ni-Fe). A uniform field distribution within an area indicates a single grain, whereas a discontinuous structure represented by sudden jumps in magnitude and/or direction of the field vectors indicates a grain boundary. The MRH scans the sample at regular intervals by means of a computer-controlled mechanical scanner, and the local field values detected can be stored in a computer for subsequent processing. The magnitudes and directions of the vectors computed from the components detected by a pair of MRHs controlled by a minicomputer were plotted with a high-resolution plotter. The plots showed that most of the grains (approximately 90%) in the samples were detected. The correlation between the grain orientation and the vector magnitude, and the effect of surface defects on the samples, were also studied